2008
DOI: 10.1128/aem.00741-08
|View full text |Cite
|
Sign up to set email alerts
|

The Obligate Mutualist Wigglesworthia glossinidia Influences Reproduction, Digestion, and Immunity Processes of Its Host, the Tsetse Fly

Abstract: Tsetse flies (Diptera: Glossinidae) are vectors for trypanosome parasites, the agents of the deadly sleeping sickness disease in Africa. Tsetse also harbor two maternally transmitted enteric mutualist endosymbionts: the primary intracellular obligate Wigglesworthia glossinidia and the secondary commensal Sodalis glossinidius. Both endosymbionts are transmitted to the intrauterine progeny through the milk gland secretions of the viviparous female. We administered various antibiotics either continuously by per o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
281
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(292 citation statements)
references
References 39 publications
6
281
1
4
Order By: Relevance
“…Recent evidence is mounting that the transmission of vector‐borne pathogens can be inhibited by other vector‐associated microbes (Sinkins, 2013). In the past decade, studies have shown that certain microbes associated with insect vectors could be used to mediate the transmission of diseases including those transmitted by mosquitoes (Capone et al., 2013; Cirimotich et al., 2011; Dong, Manfredini, & Dimopoulos, 2009; Mourya, Pidiyar, Patole, Gokhale, & Shouche, 2002; Ramirez et al., 2014; Tchioffo et al., 2013; Xi, Ramirez, & Dimopoulos, 2008), tsetse flies (Pais, Lohs, Wu, Wang, & Aksoy, 2008; Wang, Wu, Yang, & Aksoy, 2009; Weiss, Wang, Maltz, Wu, & Aksoy, 2013), sand flies (Sant'Anna et al., 2014), and ticks (Gall et al., 2016; Narasimhan et al., 2014). The most striking example is the inhibition by bacterium Wolbachia pipientis of virus and parasite infection in mosquito vectors (Bian, Xu, Lu, Xie, & Xi, 2010; Blagrove, Arias‐Goeta, Di Genua, Failloux, & Sinkins, 2013; Frentiu et al., 2014; van den Hurk et al., 2012; Hussain et al., 2012; Moreira et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence is mounting that the transmission of vector‐borne pathogens can be inhibited by other vector‐associated microbes (Sinkins, 2013). In the past decade, studies have shown that certain microbes associated with insect vectors could be used to mediate the transmission of diseases including those transmitted by mosquitoes (Capone et al., 2013; Cirimotich et al., 2011; Dong, Manfredini, & Dimopoulos, 2009; Mourya, Pidiyar, Patole, Gokhale, & Shouche, 2002; Ramirez et al., 2014; Tchioffo et al., 2013; Xi, Ramirez, & Dimopoulos, 2008), tsetse flies (Pais, Lohs, Wu, Wang, & Aksoy, 2008; Wang, Wu, Yang, & Aksoy, 2009; Weiss, Wang, Maltz, Wu, & Aksoy, 2013), sand flies (Sant'Anna et al., 2014), and ticks (Gall et al., 2016; Narasimhan et al., 2014). The most striking example is the inhibition by bacterium Wolbachia pipientis of virus and parasite infection in mosquito vectors (Bian, Xu, Lu, Xie, & Xi, 2010; Blagrove, Arias‐Goeta, Di Genua, Failloux, & Sinkins, 2013; Frentiu et al., 2014; van den Hurk et al., 2012; Hussain et al., 2012; Moreira et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Removing Wigglesworthia symbionts in tse-tse flies makes them more susceptible to trypanosome infection [18]. Recent investigations suggest that the interaction is mediated by a host peptidoglycan recognition protein that is involved both in host immune tolerance to the obligate symbiont and in the trypanosome infection process [19].…”
Section: Are Heritable Endosymbionts Affecting Important Ecological Tmentioning
confidence: 99%
“…Particularly frequent in species thriving on nutritionally unbalanced environments, such endosymbioses are believed to impact several aspects of host biology, including physiology, immunity and reproduction [2][3][4][5][6][7][8]. They ensure a nutritional complementation of the host diet by providing vitamins and essential amino acids [3,7,9,10], thus greatly improving host fitness [2,3,7,11,12].…”
Section: Introductionmentioning
confidence: 99%